1982
DOI: 10.1084/jem.155.2.605
|View full text |Cite
|
Sign up to set email alerts
|

Lack of oral tolerance in C3H/HeJ mice.

Abstract: Oral tolerance, or systemic unresponsiveness to ingested antigen, was first described at the turn of the century; however, the underlying mechanisms involved have only recently been studied in detail (1). Several investigations (2-4) have shown that oral administration of sheep erythrocytes (SRBC) to'mice for prolonged periods results in systemic unresponsiveness to this antigen. The lack of responsiveness has been ascribed to T suppressor (Ts) cells (5), suppressor factors (3, 5), and immune complexes (2) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2
1

Year Published

1983
1983
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 12 publications
(6 reference statements)
4
46
2
1
Order By: Relevance
“…This suggests that TLR4 signaling by the intestinal microflora is necessary for proper immune homeostasis both in the gut and systemically (34). Our findings were foreshadowed by earlier studies, predating the identification of TLRs, which demonstrated that nonresponsiveness to SRBC could be induced in C3H/HeN but not in LPS-nonresponsive C3H/HeJ mice (35,36). The authors insightfully proposed that the failure to induce nonresponsiveness was related to the absence of a flora-induced immunoregulatory cell population in C3H/HeJ mice.…”
Section: Tlr Involvement In Responses To Intestinal Agssupporting
confidence: 62%
“…This suggests that TLR4 signaling by the intestinal microflora is necessary for proper immune homeostasis both in the gut and systemically (34). Our findings were foreshadowed by earlier studies, predating the identification of TLRs, which demonstrated that nonresponsiveness to SRBC could be induced in C3H/HeN but not in LPS-nonresponsive C3H/HeJ mice (35,36). The authors insightfully proposed that the failure to induce nonresponsiveness was related to the absence of a flora-induced immunoregulatory cell population in C3H/HeJ mice.…”
Section: Tlr Involvement In Responses To Intestinal Agssupporting
confidence: 62%
“…Oral tolerance is mediated primarily by TGF-␤1, as anti-TGF-␤1 neutralizing Ab abrogates tolerance induction (69). Moreover, LPS-mediated signaling through the TLR-4 is thought to be obligatory for the induction of oral tolerance, because it was found to be absent in C3H/HeJ mice that are defective in LPS responses due to mutations within the TLR-4 gene (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Mice that lack a constant source of LPS entering their liver (germfree mice) have reduced expression of the adhesion molecule ICAM-1 in their livers, and a normal level of expression can be restored by the intragastric inoculation of cecal microflora from normal mice (20). Both germfree mice and TLR-4-deficient mice (21) show defective oral tolerance, whereas other studies show that the liver is involved in this process (22,23).…”
Section: A Ctivated Cd8mentioning
confidence: 99%